Some Generalized Formulas of Hadamard-Type Fractional Integral Inequalities - Xiujun Zhang; Ghulam Farid; Hafsa Yasmeen; Kamsing Nonlaopon (Journal of Function Spaces)
This paper is aimed at establishing the generalized forms of Riemann-Liouville fractional inequalities of the Hadamard type for a class of functions known as strongly exponentially α,h−m-p-convex functions. These inequalities provide some general formulas from which one can get associated inequalities for various types of exponentially convex and strongly convex functions. Refinements of well-known inequalities are also deducible from the established theorems.